The effectiveness of A training Program to Raise the Knowledge of Teachers and Mothers of Children with Autism Spectrum Disorder with Applied Behavior Analysis Strategies - إبراهيم عبداللاه أحمد فايزة (Journal of College of Education, 2020)
The study aimed to identify the effectiveness of a training program to raise the knowledge of teachers and mothers with autism spectrum disorder with strategies for applied behavior analysis, and the study sample consisted of (160) teachers and mothers with teachers and mothers with autism spectrum disorder in centers and institutions of day care in the city of Al-Kharj, Saudi Arabia, and was They were divided into two groups, one of them was an experimental group, counting them (80), and the second was a control group counting them (80), and the researcher used the experimental method, and the training program (the preparation of the researcher) The proposed program in this study included (12) training sessions that were presented during (4) weeks, and a scale Applied behavior analysis strategies for children with autism spectrum disorder (researcher’s preparation) The results of the study reached the effectiveness of the training program as it contributed statistically significant in raising the level of knowledge of teachers and mothers with autism spectrum disorder with strategies of applied behavior analysis of the target sample in this study, and the presence of a statistically significant difference between the averages of the scores (parameters - mothers) of the experimental and control group On the scale of strategies of applied behavior analysis in post measurement in favor of the experimental group (parameters - mothers) in the pre and post measurements in favor of post measurement, and the absence of statistically significant differences between the averages of the degrees of the teachers and the mean levels of the mothers in the control group on the scale of the strategies of analyzing the applied behavior in the tribal measurements And the dimensions, the obstacles that teachers face regarding the application of strategies in day care centers in Al-Kharj from their point of view.